Pematahan Dormansi Benih Cabai Rawit Lokal (Capsicum Frutescens L.) dengan Perlakuan KNO3 - Gaudensiana Laisbuke (Fakultas Pertanian, Universitas Timor, 2022)
This study aims to determinethe right concentration of KNO3 for breking the dormancy of cayenne pepper seeds and the length of time soaking in the right KNO3 solution for breking the dormancy of cayenne pepper seeds. This research was carriedout in January-February 2022 in the experimental field of the faculty of agriculture, university of Timor sasi village, kefamenanu city district, north central Timor Regency. This study used a completely randomized design (CRD). The first factor is the concentration of KNO3 (K), whit level 3, namely: (K0) KNO3 1%, (K1) KNO3 2%, (K2) KNO3 3% the second factor is the immersion time (C0) 0 hours, (C1) 12 hours, (C2) 24 hours the results showed that KNO3 3% concentration in increasing germination (88,67%), and maximum growth potential (88,17%) and vigor index (60,67%) the 12 hour soaking treatment was the best treatment in increasing the germination and growth of cayenne pepper seeds.